Benzenesulfonyl thiazoloimines as unique multitargeting antibacterial agents towards Enterococcus faecalis - Zhou, Xue-Mei; Hu, Yuan-Yuan; Fang, Bo; Zhou, Cheng-He (European journal of medicinal chemistry, 2023)
New efficient antimicrobial agents are urgently needed to combat invasive multidrug-resistant pathogens infections. Structurally unique benzenesulfonyl thiazoloimines (BSTIs) were exploited as novel potential antibacterial victors to confront terrific drug resistance. Some developed BSTIs exerted effectively antimicrobial efficacy against the tested strains. Notably, 2-pyridyl BSTI 14d exhibited good antibacterial activity against E. faecalis with MIC value of 1 μg/mL, which was superior to sulfathiazole and norfloxacin. The most active compound 14d not only showed rapid bactericidal properties and impeded E. faecalis biofilm formation to effectually relieve the development of drug resistance, but also performed low toxicity toward human red blood cells, human normal squamous epithelial cells and human non-neoplastic colon epithelial cells. Mechanistic investigation demonstrated that molecule 14d could exert efficient membrane destruction leading to the leakage of intracellular materials and metabolism inhibition, cause oxidative damage of E. faecalis through accumulation of excess reactive oxygen species and reduction of glutathione activity, and intercalate into DNA to hinder replication of DNA. Molecular docking indicated that the formation of 14d-dihydrofolate synthetase supramolecular complex could hinder the function of this enzyme. ADME analysis displayed that compound 14d possessed promising pharmacokinetic properties. These findings suggested that the newly developed benzenesulfonyl thiazoloimines with multitargeting antibacterial potential provided a new possibility for evading resistance. [Display omitted] •Novel benzenesulfonyl thiazoloimines with multitargeting antibacterial potential were developed.•Some compounds showed superior antibacterial efficacy to sulfathiazole and norfloxacin.•Active molecule 14d showed low cytotoxicity, no obvious resistance and good bioavailability.•Compound 14d could effectively target membrane, DNA and dihydrofolate synthetase, and cause oxidative damage.